The naked now learning to see as the mystics see - Rohr, Richard 1943- (New York, NY Crossroad Publ. Company, 2009)
Preface -- Why I am writing this book -- The gift is already given -- When you surrender to fear and distraction -- When you joyfully surrender to God -- Discover your birthright -- Prayer-practicing heaven now -- The great unsaying -- Three ways to view the sunset -- The urgent need for contemplative seeing -- What it means to be a mystic -- We should have "known" better -- Knowing worse : all-or-nothing thinking -- Knowing better : contemplation and presence -- Mystical Christianity : a critique from within -- A lesson from the monks -- The limitations of individualism -- A debate everyone can win -- Glimpses of wonder : the quest is begun -- But we have to make judgments, don't we? -- We see what we are ready to see -- The radical perceptual shift : is it true? -- Yes, but -- Not many things, but one thing -- Getting thrown off your horse : sudden conversion -- Gradual conversion -- How Martha becomes Mary : willfulness and willingness -- What about Jesus? -- The prayer of Jesus -- Not here, not there -- The two heels of a Christian achilles -- Conversion : begin by changing the seer -- Healing the observer -- Three levels of conversion -- Change your mind -- The ego hates change -- Different religions, same ego resistance -- Inertia resists change -- Heaven and hell : you must change again and again -- Things "too good to be true" : from polarity thinking to prayer -- Reframing false dilemmas -- Alternative consciousness -- Prayer is resonance -- Experience impossible and improbable things -- The lost tradition -- The decline of contemplation -- More recent rediscoveries -- Faith is more how to believe than what to believe -- Opening the door : great love and great suffering -- What nondual thinking is not -- The watchful gaze : what do we mean by being "awake"? -- The meaning of spiritual love -- Sinners, mystics, and astrophysicists : how to celebrate paradox -- The value of paradox -- Greek logic -- Trinity -- Physics and astrophysics -- What it means to follow Jesus -- What every good leader knows -- The principle of likeness : in the end, it all comes down to this -- Appendices
Includes bibliographical references
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Mysticism; Spiritual Life -- Christianity